Sosialisasi Pembuatan Kerajinan Dari Stik Es Krim Untuk Menumbuhkan Kreativitas Pada Anak- Anak Desa Batang Ara Kecamatan Bandar Pusaka - Surya Ramadhan; Rahma Aulia Batu Bara; Khairunnisa; Khairani Sakdiah (peduli riset dan pengabdian masyarakat, 2024)
Make ice cream stick crafts that are worth salling. That aim of the PKM student creativity in using used goods in the form of ice cream sticks to become useful items and have artistic value. In developing childten’s skills as a provision for creativity and developing a sense of beauty and the ability to appreciate arts and crafts. Make ice cream stick crafts that are worth selling. The aim of the PKM student creativity program is to inspire children in Batang Ara village to be more creative in using used goods in the form of ice cream sticks to become useful items and have artistic value. In developing children's skills as a provision for creativity and developing a sense of beauty and the ability to appreciate arts and crafts. Selection of materials and provision of facilities and infrastructure to support the production process is the final step. The process (creation), namely how to make houses and stationery from ice cream sticks, starts from arranging materials and tools. The final product or result is the transformation of ice cream sticks into houses and stationery. The final stage of evaluation, which is carried out after production is complete. This craft has selling value, and can teach children how to innovate and be creative in the process of processing used goods in the form of ice cream sticks into items that can be used. Make ice cream stick crafts that are worth salling. That aim of the PKM student creativity in using used goods in the form of ice cream sticks to become useful items and have artistic value. In developing childten’s skills as a provision for creativity and developing a sense of beauty and the ability to appreciate arts and crafts. Make ice cream stick crafts that are worth selling. The aim of the PKM student creativity program is to inspire children in Batang Ara village to be more creative in using used goods in the form of ice cream sticks to become useful items and have artistic value. In developing children's skills as a provision for creativity and developing a sense of beauty and the ability to appreciate arts and crafts. Selection of materials and provision of facilities and infrastructure to support the production process is the final step. The process (creation), namely how to make houses and stationery from ice cream sticks, starts from arranging materials and tools. The final product or result is the transformation of ice cream sticks into houses and stationery. The final stage of evaluation, which is carried out after production is complete. This craft has selling value, and can teach children how to innovate and be creative in the process of processing used goods in the form of ice cream sticks into items that can be used.